Tradisi Gawe Mensajiq di Lombok, Indonesia: Identifikasi Nilai-Nilai Sosial-Keagamaan dan Eksistensinya di Era Digital - Ningsih, Ayu Sadana Prihatin; Deviana Mayasari; Zedi Muttaqin; Malami Muhammad Garba; Ravindra Ashok Jadhav (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2024)
Socio-religious values in a tradition play an important role in people's lives providing insight into the impact of globalization on cultural values in society. Although the existing literature mostly discusses various socio-cultural values in Indonesia, this article specifically focuses on the socio-religious values embedded in the gawe mensajiq tradition which is celebrated in the bale beleq (traditional house) geding kedaton by the people of Sukadana Village, Terara District, East Lombok Regency, and how this tradition is preserved. Using qualitative approach, this study was conducted in Sukadana Village, Terara District, East Lombok, West Nusa Tenggara. Data collection was carried out through observation, interviews and documentation. There are five informants involved in this study, consisting of two bale beleq traditional leaders, another two religious leaders, and a number of members of the local community. The results showed the identification of socio-religious values in the celebration of the gawe mensajiq tradition in the geding kedaton traditional house accompanied by an analysis of its development in the digital era and efforts to preserve this cultural heritage. Some of the socio-religious values inherent in the mensajiq tradition include piety, ethics and morality, purity, cooperation, material values, communal spirit, fostering relationships, tolerance, honor and responsibility. The tradition of gawe mensajiq in the Sukadana Village community has become a cultural practice that is rooted and embraced by residents. This tradition is considered a heritage that has been passed down from generation to generation thus fostering pride in the Sukadana community. The people of Sukadana consider gawe mensajiq to have positive values thus motivating them to continue to preserve this cultural tradition.